2020
DOI: 10.2147/cmar.s245794
|View full text |Cite
|
Sign up to set email alerts
|

<p>Short-Term Clinical and Oncological Outcome of Prolonging Operation Interval After Neoadjuvant Chemoradiotherapy for Locally Advanced Middle and Low Rectal Cancer</p>

Abstract: The purpose of this study is to evaluate the short-term clinical and oncological outcome of prolonging operation interval to 11 weeks after the end of radiotherapy for locally advanced middle and low rectal cancer. Methods: A total of 123 patients with stage II/III (cT3/T4 or N+) low and middle rectal cancer who had undergone operation after neoadjuvant chemoradiotherapy were selected. According to the interval time between the last radiotherapy and operation, they were assigned to a short-interval group (SG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Most of the retrospective studies already cited in this review have not reported a difference in perioperative outcomes or surrogate markers for a challenging operation (e.g., OR time, estimated blood loss [EBL]), however, the differences between short and long RSI in many of these studies are typically measured in weeks and do not reflect operating on patients 1-2 years following radiation. 30,34,37,38,[40][41][42][43] that a longer interval before surgery did increase operative time and EBL, but this was only true in the group who received TNT followed by proctectomy in the Xu study. 35,67 However, Huntington and colleagues analyzed over 6300 patients from the National Cancer Database and found that patients with an RSI > 80 days were associated with higher rates of positive surgical margins and lower rates of sphincter preservation and survival, even after adjusting for potential confounding factors.…”
Section: Question 2: Do Increased Rates Of Pcr Translate To Improved ...mentioning
confidence: 83%
See 2 more Smart Citations
“…Most of the retrospective studies already cited in this review have not reported a difference in perioperative outcomes or surrogate markers for a challenging operation (e.g., OR time, estimated blood loss [EBL]), however, the differences between short and long RSI in many of these studies are typically measured in weeks and do not reflect operating on patients 1-2 years following radiation. 30,34,37,38,[40][41][42][43] that a longer interval before surgery did increase operative time and EBL, but this was only true in the group who received TNT followed by proctectomy in the Xu study. 35,67 However, Huntington and colleagues analyzed over 6300 patients from the National Cancer Database and found that patients with an RSI > 80 days were associated with higher rates of positive surgical margins and lower rates of sphincter preservation and survival, even after adjusting for potential confounding factors.…”
Section: Question 2: Do Increased Rates Of Pcr Translate To Improved ...mentioning
confidence: 83%
“…[29][30][31][32][33][34][35][36] Conversely, several other observational studies demonstrated that RSI length did not impact rates of pCR. [37][38][39][40][41][42][43][44] While well-intended, observational studies are subject to confounding variables that may obfuscate the effects of the RSI.…”
Section: Question 1: Does a Longer Rsi Improve Rates Of Pcr And Does ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node dissection is the focus of surgery, and the prognostic survival of patients is closely related to the degree of lymph node dissection [24] . An increased number of positive lymph nodes often indicates a high chance of recurrence and metastasis and a poor prognosis [25] . The AJCC proposes that the detection of ≥12 lymph nodes can improve the accuracy of postoperative staging of colorectal cancer and help determine the presence or absence of lymph node metastasis [26] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest global statistics, there were over 700,000 new cases and over 300,000 deaths in 2020 (1). Due to the lack of obvious symptoms in the preliminary stage, a great number of patients are already at clinical stage II and III when they are first diagnosed, which is defined as locally advanced rectal cancer (LARC) (2). For LARC, the standard treatment is neoadjuvant chemoradiotherapy and total mesorectal excision (TME), followed by postoperative adjuvant chemotherapy (3).…”
Section: Introductionmentioning
confidence: 99%